State or nature? Formal vs. informal sanctioning in the voluntary provision of public goods - Kenju Kamei; Louis Putterman; Jean-Robert Tyran (Brown University, Department of Economics, 2011)
The sanctioning of norm-violating behavior by an effective formal authority is an efficient solution for social dilemmas. It is in the self-interest of voters and is often favorably contrasted with letting citizens take punishment into their own hands. Allowing informal sanctions, by contrast, not only comes with a danger that punishments will be misapplied, but also should have no efficiency benefit under standard assumptions of self-interested agents. We experimentally investigate the relative effectiveness of formal vs. informal sanctions in the voluntary provision of public goods. Unsurprisingly, we find that effective formal sanctions are popular and efficient when they are free to impose. Surprisingly, we find that informal sanctions are often more popular and more efficient when effective formal sanctions entail a modest cost. The reason is that informal sanctions achieve more efficient outcomes than theory predicts, especially when the mechanism is chosen by voting.
Keywords: C92; C91; D03; D71; H41; 330; sanction; social dilemma; public goods; voluntary contribution mechanism; punishment; experiment